Penggunaan Finger Print Sebagai Upaya Pencegahan Fraud Dalam Penjaminan Pasien Pengguna JKN : Studi Kasus Di RSIA X Kota Kupang - Maria Sumiati Amabi; Wahyuni Arumsari; Dwi Nur Siti Marchamah (Indonesian Journal of Health Community, 2024)
Fraud in health insurance significantly burdens the financing of health services. One of the fraud prevention innovations that has been developed and implemented by health service providers is the use of fingerprints. This research uses a qualitative method with a case study approach, aiming to explore the use of finger prints in legalizing BPJS Kesehatan patient guarantee letters as an effort to prevent fraud. The research was conducted at RSIA X Kupang City. Researchers carry out assessments, determine diagnosis, plan actions and initiate actions that have been taken. The case with the initials Mrs. I came with a referral from FKTP to carry out a pregnancy check, but it was indicated that She has used another participant's JKN-KIS card. Results of the evaluation, it was found that fraud was able to be prevented by RSIA. The actions taken by officers in the outpatient registration section at RSIA based on SOP, which is a derivative of the cooperation agreement between RSIA and BPJS Kesehatan. However, participants who do not meet these requirements have received services at FKTP as proven by the reference letter. This is indeed a challenge for BPJS Health and FKTP to innovate to overcome this problem.